B)40 because (4)*50/5 is (4)*10
- Multiply (-2x-4) by -5:
[(-5)(-2x) + (-5)(-4)] +5x - 4 = -29
= 10x+20+5x-4=-29
- Combine Like Terms:
(10x+5x) + (20-4) = -29
15x+16=-29
- Subtract 16 from each side
15x+16 -16 = -29 -16
15x = -45
x = -3
Hello from MrBillDoesMath!
Answer:
x = 1/2 (1 +\- i sqrt(23))
Discussion:
x \3x - 2 = (x/3)*x - 2 = (x^2)/3 - 2 (*)
1 \3x - 4 = (1/3)x - 4 (**)
(*) = (**) =>
(x^2)/3 -2 = (1/3)x - 4 => multiply both sides by 3
x^2 - 6 = x - 12 => subtract x from both sides
x^2 -x -6 = -12 => add 12 to both sides
x^2-x +6 = 0
Using the quadratic formula gives:
x = 1/2 (1 +\- i sqrt(23))
Thank you,
MrB
<h3>
Answer:</h3>
- y = -(x -3)² +3 . . . . (agrees with your answer)
- see the attachment for a graph
<h3>
Step-by-step explanation:</h3>
Factoring the leading -1 from the first two terms, we have ...
... y = -(x² -6x) -6
Adding 9 inside parentheses to complete the square, then adding the opposite amount outside parentheses, we have ...
... y = -(x² -6x +9) -6 +9
... y = -(x -3)² +3